The Impact of Drug Properties and Severity of Obesity on Renal Drug Clearance Through Glomerular Filtration and Active Tubular Secretion: A Systematic Analysis Using PBPK Modeling - Zhang, Tan; Calvier, Elisa A. M.; Krekels, Elke H. J.; Knibbe, Catherijne A. J. (Pharmaceutical research, 2025)
Objective The influence of obesity on renal drug clearance (CLr) remains difficult to predict. This study quantifies obesity-related alterations in CLr for drugs eliminated via glomerular filtration (GF/CL GF ) and active tubular secretion (ATS/CL ATS ) and assesses the systematic accuracy of dosing based on allometric scaling with an exponent of 0.75 or flat dosing (exponent of 0). Methods A physiologically-based pharmacokinetic (PBPK) approach was used to simulate CL GF and CL ATS for 11,520 hypothetical drugs in typical subjects with body mass index (BMI) between 20 and 60. Correlations between changes in CL GF and CL ATS and subject or drug properties were investigated. Moreover, for each drug, CLr values scaled to individuals with obesity from CLr values in normal-weight individuals were compared to PBPK predictions of CLr. Systematic scaling accuracy was defined as the prediction error being less than ± 30% for all drugs. Results CLr through GF and ATS increased with BMI, albeit to different extents, depending on drug properties. When BMI was below 30 kg/m 2 and transporter activity remained unchanged, the CLr between subjects of normal weight and with overweight or obesity differed less than 30% and both scaling methods were systematically accurate. For individuals with higher BMI, drug properties need to be taken into account when defining scenarios of systematic scaling accuracy. Conclusion In individuals with a BMI above 30 kg/m 2 , neither 0.75 allometric scaling nor no scaling (flat dosing) is systematically accurate for renally cleared drugs. Strategies are provided to define systematic scaling accuracy a priori , based on subject and drug properties.